My beautiful girl Mari [videorecording (DVD)] - Lee, Sung-gang (ADV Films, 2005)
A young boy lives in a seaside village with his mother and grandmother. One day he finds a mysterious marble with the image of a beautiful girl inside, and he begins to fall into a world of fantasy.